Drosophila polypyrimidine-tract binding protein (PTB) functions specifically in the male germline - Robida, Mark D. (Oxford University Press, 2003)
The mammalian polypyrimidine-tract binding protein (PTB), which is a heterogeneous ribonucleoprotein, is ubiquitously expressed. Unexpectedly, we found that, in Drosophila melanogaster, the abundant PTB transcript is present only in males (third instar larval, pupal and adult stages) and in adult flies is restricted to the germline. Most importantly, a signal from the somatic sex-determination pathway that is dependent on the male-specific isoform of the doublesex protein (DSX(M)) regulates PTB, providing evidence for the necessity of soma–germline communication in the differentiation of the male germline. Analysis of a P-element insertion directly links PTB function with male fertility. Specifically, loss of dmPTB affects spermatid differentiation, resulting in the accumulation of cysts with elongated spermatids without producing fully separated motile sperms. This male-specific expression of PTB is conserved in D.virilis. Thus, PTB appears to be a particularly potent downstream target of the sex-determination pathway in the male germline, since it can regulate multiple mRNAs.